IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 KAUM LANSIA DI KELURAHAN KEBON KOSONG JAKARTA PUSAT - Joana Selviana, (2022)
The government as a decision-maker took various efforts in terms of suppressing the spread of the covid-19 virus in the community, one of which was the vaccination program that was already running. The government requires every citizen to vaccinate in terms of suppressing the spread covid virus in the community up to 3 times the vaccine. The elderly are a special concern for the government because they are at a vulnerable age. The author then motivated this research on the vaccination process for the elderly. The research location taken by the author is in Kebon Blank Village. This study aims to find out what are the obstacles in implementing the Covid-19 vaccination policy in the Kebon Blank village, determine the level of knowledge about the quality of the Covid-19 vaccination socialization for the elderly in the Kebon Blank Village, Central Jakarta, provide information about various factors that determine the quality of socialization of the Covid-19 vaccine to the elderly at the Kebon Blank Village, Central Jakarta. Then it is hoped that this research can become knowledge and also become a source of information so that the public can add insight into understanding vaccines and become a reference and data submission for further research. The study used qualitative methods with a descriptive analytical approach and data collection techniques through observation and interviews, then triangulated and included in the discussion. This research on vaccination policy in Kebon Village found the result that in Kebon Blank Village the vaccination process had been running in accordance with the government program with the responsibility for its implementation being handed over to the Kebon Blank Village Health Center. Vaccination for the elderly who are the object of research has also been running but there is no maximum socialization so that there are still many elderly people who have not received information about the implementation of the vaccine.